Optimization of Water Spinach Growth (Ipomoea aquatica) in The Budikdamber System as A Solution for Eco-Friendly Catfish Cultivation (Clarias sp.) in Central Tapanuli Regency - Khobir, Muhamad Latiful; Rumondang, Anne; J, Mhd. Aidil Huda; Basriani, Anna; Batubara, Muhammad Iqbal (Mantis Journal of Fisheries, 2025)
This study aims to evaluate the effectiveness of an innovative filtration system in bucket aquaponics “budikdamber” on the growth performance of water spinach (Ipomoea reptans) at three different locations: Tapian Nauli, STPK Matauli, and the Central Bureau of Statistics of Central Tapanuli (BPS). The experimental design was a randomized block design with two treatments (conventional and innovative filtration systems) and three replications. Observed parameters included plant height, number of leaves, and daily growth rate. The results showed that using the innovative filtration system significantly enhanced plant growth compared to the conventional system. The innovative system recorded the highest plant height at Tapian Nauli, reaching 26.3±1.7 cm and 11.5±0.9 leaves per plant, with a daily growth rate of 3.62%. The innovative filtration system improved water quality through mechanical and biological filters that supported the conversion of ammonia into plant-available nitrate. Thus, this system can be an adaptive and sustainable technology to enhance budikdamber productivity, particularly in coastal and rural areas.